Intrapartum endotracheal intubation in fetuses with airway obstruction. Two first cases of EXIT surgery at the Rebagliati Hospital - EsSalud - Huerta Sáenz, Igor Hermann (2022)
Two cases of pregnant women in the third trimester of gestation referred formanagement of fetal cervical tumor with airway obstruction are presented. Thecases were scheduled for EXIT (ex-utero intrapartum treatment), fetal surgerywhich allowed controlled intrapartum orotracheal intubation avoiding the periodof hypoxia and potential asphyxia that would occur with the conventional neonatalprocedure. The neonates were subsequently operated on by head and neck surgeonsfor reduction of the cervical mass. It is suggested to consider this procedure in caseswhere severe airway obstruction is suspected and to refer them to centers that havea fetal surgery unit with a multidisciplinary medical team.